2022
DOI: 10.3390/electronics11223653
|View full text |Cite
|
Sign up to set email alerts
|

Quiescent Optical Solitons with Cubic–Quartic and Generalized Cubic–Quartic Nonlinearity

Abstract: The enhanced Kudryashov’s approach retrieves quiescent bright, dark, and singular solitons to the governing model that is considered with cubic–quartic form of self-phase modulation. The algorithm however fails to retrieve stationary solitons when the nonlinearity is the generalized version of the cubic–quartic form. The current analysis is conducted with a direct approach without an intermediary phase-portrait analysis as in the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Step-3: Through the amalgamation of Equation (7) with Equations ( 8) and ( 9), followed by their substitution into Equation (3), we arrive at a polynomial equation encompassing the variables F(ξ ) and G(ξ ). The coefficients derived from this polynomial equation furnish the parameter values for Eqs.…”
Section: Projective Riccati Equation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Step-3: Through the amalgamation of Equation (7) with Equations ( 8) and ( 9), followed by their substitution into Equation (3), we arrive at a polynomial equation encompassing the variables F(ξ ) and G(ξ ). The coefficients derived from this polynomial equation furnish the parameter values for Eqs.…”
Section: Projective Riccati Equation Approachmentioning
confidence: 99%
“…The evolution of quiescent optical solitons has gained momentum and extreme importance ever since its first appearance about two decades ago [1][2][3][4][5]. The study of such solitons with nonlinear chromatic dispersion (CD) revealed quite a few results that have been reported all across the board [6][7][8][9][10]. Several models with nonlinear CD and various forms of self-phase modulation (SPM) structures have been studied [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%